2007
DOI: 10.1002/biof.5520300302
|View full text |Cite
|
Sign up to set email alerts
|

Brazilin and the extract from Caesalpinia sappan L. protect oxidative injury through the expression of heme oxygenase‐1

Abstract: In this study, we examined the protective effects of Caesalpinia sappan L. and its major component, brazilin, against tert-butylhydroperoxide (t-BHP)-induced cell death in House Ear Institute-Organ of Corti 1 (HEI-OC1) cells. We found that the extract of C. sappan L. and brazilin induced antioxidant response element (ARE)-luciferase activity and heme oxygenase-1 (HO-1) expression in a concentration-dependent manner. The inductive effect of brazilin was more potent than the extract of C. sappan L. and the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Antioxidant DPPH radical scavenging assay Sasaki et al; [15] Batubara et al [14] Ferric reduction assay Sasaki et al [15] Linoleic acid peroxidation assay Sasaki et al [15] Antibacterial Zone of inhibition Kim et al; [33] Srinivasan et al [32] MIC/MBC Xu and Lee; [5] Batubara et al; [14] Nirmal & Panichayupakaranant [13] Anti-inflammatory LPS-induced NO production Sasaki et al; [15] Hu et al; [39] Washiyama et al; [6] Wu et al [40] Inhibition of iNOS gene expression Sasaki et al; [15] Hu et al; [39] Washiyama et al; [6] Bae et al [3] Hemeoxygenase-1 expression Hu et al; [39] Choi et al [50] Bilirubin production Hu et al [39] Prostaglandin E 2 production Hu et al; [39] Wang et al [22] Tumor necrosis factor-a production Hu et al; [39] Wu et al; [40] Wang et al [22] Interlukin (IL)-1b production Hu et al; [39] Wu et al; [40] Wang et al [22] Nucler factor (NF-k B) expression Bae et al; [3] Wang et al; [22] Toegel et al; [1] Lee et al [7] Activator protein-1 expression Bae et al [3] …”
Section: Pharmacological Activities Methods/model System Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidant DPPH radical scavenging assay Sasaki et al; [15] Batubara et al [14] Ferric reduction assay Sasaki et al [15] Linoleic acid peroxidation assay Sasaki et al [15] Antibacterial Zone of inhibition Kim et al; [33] Srinivasan et al [32] MIC/MBC Xu and Lee; [5] Batubara et al; [14] Nirmal & Panichayupakaranant [13] Anti-inflammatory LPS-induced NO production Sasaki et al; [15] Hu et al; [39] Washiyama et al; [6] Wu et al [40] Inhibition of iNOS gene expression Sasaki et al; [15] Hu et al; [39] Washiyama et al; [6] Bae et al [3] Hemeoxygenase-1 expression Hu et al; [39] Choi et al [50] Bilirubin production Hu et al [39] Prostaglandin E 2 production Hu et al; [39] Wang et al [22] Tumor necrosis factor-a production Hu et al; [39] Wu et al; [40] Wang et al [22] Interlukin (IL)-1b production Hu et al; [39] Wu et al; [40] Wang et al [22] Nucler factor (NF-k B) expression Bae et al; [3] Wang et al; [22] Toegel et al; [1] Lee et al [7] Activator protein-1 expression Bae et al [3] …”
Section: Pharmacological Activities Methods/model System Referencesmentioning
confidence: 99%
“…The antioxidant activity of brazilin (IC 50 8.8 mM) was not significantly different from protosappanin A (9.1 mM) and (+)-catechin (10.2 mM). The antioxidant activity of brazilin and protosappanin A were higher than sappanone B (IC 50 14.5 mM).…”
Section: Antiacne Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…This plant was used in Vietnamese traditional medicine for the treatment of menstrual and post-partum hematometra, trauma blood static, dizziness, post-partum blood losses, bloody dysentery, enteralgia, intestinal hemorrhage, infectious diarrhea, and for washing wounds (Bich, 1999). Many reports showed that the main components in the heartwood of C. sappan are phenolics with anti-inflammatory, antibacterial, and anti-influenza activities (Choi et al, 2007;Cuong et al, 2012;Kim et al, 2012;Namikoshi et al, 1987;Shimokawa et al, 1985;Washiyama et al, 2009). Nguyen et al (2004) reported that the methanolic extract of the heartwood of C. sappan collected in Vietnam exhibited significant XO inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The major active components in C. sappan are phenolics of four structural subtypes: brazilin, chalcone, protosappanin, and homoisoflavonoids [1015]. An ethanol extract of C. sappan ameliorated hypercholesterolemia in C57BL/6 mice and suppressed inflammatory responses in human umbilical vein endothelial cells (HUVECs) through an antioxidant mechanism [11]. Compounds with a sappanchalcone skeleton exhibited antiinflammatory, antibacterial, and antiinfluenza activities [1215].…”
Section: Introductionmentioning
confidence: 99%